Water Quality and It's Effect on Seaweed Cultivation in Pari Island, Kepulauan Seribu DKI Jakarta. (April 2018) - Warnadi, S; Setyaningsih, A I; Kasih, W A
Abstract: This research aims to determine the effect of water quality on the sustainibility of seaweed cultivation in Pari Island, Kepulauan Seribu DKI Jakarta. Based on the results of research that the quality of waters in Goba Pari Island were suitable for seaweed cultivation. The inhibiting parameters in all four goba in the cluster of Pari Islands are the current and temperature parameters in all goba when compared to the requirement for seaweed growth.